Determinants Of Taxpayer Compliance With Self Assessment System As A Mediation Variable During The Covid-19 Pandemic - Slamet Wahyudi (International Journal of Social Service and Research, 2022)
This study aims to empirically examine the effect of taxpayer awareness, tax service services, and tax sanctions on taxpayer compliance with the practice of a self-assessment system as a mediator during the Covid-19 pandemic. The research design used is quantitative with primary data. Respondents in this study were 216 employees at the Taman Mega Kuningan Office, South Jakarta, who were individual taxpayers registered at KPP Pratama Jakarta Setiabudi Empat. Data analysis was performed using Sequential Equation Modeling (SEM) - Lisrel 8.70 software with a tolerable error rate of 5%. The study results indicated that the direct effect on taxpayer awareness and tax service services cannot be proven, but the tax sanctions on taxpayer compliance can be proven. The immediate impact of tax sanctions cannot be demonstrated. The direct influence on taxpayer awareness and tax service services on the practice of the self-assessment system can be proven. The indirect effect of taxpayer awareness tax service services on taxpayer compliance through the self-assessment system variable can be established. In contrast, the indirect impact of tax sanctions on taxpayer compliance through the self-assessment system variable cannot be confirmed.